The Relationship Between Willingness to Disclose Personal Information and Satisfaction With the Services of the Government Agency Call Center - Maleesuwannachai, Noppon; Pomsathit, Auttapon; Kerdaroondej, Boonruang (Rattanakosin Journal of Social Sciences and Humanities, 2023)
This article presented the relationship between willingness to disclose personal information and satisfaction with the services of government agency call center using quantitative research method. Accidental sampling with a sample size of 391 online users was done. The data collection tool was an online questionnaire. The method used for data analysis was the Spearman rank correlation coefficient. The findings indicated that the willingness to disclose personal information had an average level of 3.29, with a standard deviation of 1.19. Similarly, the overall satisfaction factor had an average level of 4.00, with a standard deviation of 1.49. Moreover, there was a significant positive correlation (p < 0.001) between the willingness to disclose personal information and service satisfaction. This correlation was substantiated by a moderate relationship level, as indicated by a Spearman rank correlation coefficient of 0.419. This result serves as a reference for creating policies, strategies, work plans, and projects that focus on service delivery through the Customer Service Center for government agencies.